The Challenges of Water Management and Governance in Cities - Hofman, Jan (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Global population growth is urban growth and, therefore, most of the water-related challenges and solutions reside in cities. Unless water management and water governance processes are significantly improved within the next decade or so, cities are likely to face serious and prolonged water insecurity, urban floods, and/or heat stress, which may result in social instability and, ultimately, massive migration. Aging water infrastructure, one of the most expensive infrastructures in cities, is a relevant challenge in order to address Sustainable Development Goal (SDG) 6: clean water and sanitation, SDG 11: sustainable cities and communities, and SDG 13: climate action. The choice of good governance arrangements has important consequences for economic performance, for the well-being of citizens, and for the quality of life in urban areas. The better governance arrangements work in coordinating policies across jurisdictions and policy fields, the better the outcomes. Rapidly-changing global conditions will make future water governance more complex than ever before in human history, and expectations are that water governance and water management will change more during the next 20 years compared to the past 100 years. In this Special Issue of Water, the focus will be on practical concepts and tools for water management and water governance, with a focus on cities.